Dampening of IL-2 Function in Infants with Severe Respiratory Syncytial Virus Disease - Sananez, Inés (2018)
Background FOXP3 + regulatory T cells (Tregs) restrain the destructive potential of the immune system. We have previously reported a pronounced reduction in circulating Tregs in infants with severe respiratory syncytial virus (RSV) disease. Because interleukin-2 (IL-2) is critical for Treg growth, survival, and activity, we here analyzed IL-2 production and function in RSV-infected infants. Methods Phenotype, proliferation, IL-2 production, and IL-2 signaling in CD4 + T cells were analyzed by flow cytometry. Serum soluble CD25 levels were quantified by ELISA. Results CD4 + T cells from RSV-infected infants produced lower amounts of IL-2 and showed a reduced proliferative response compared with healthy infants. IL-2 increased CD4 + T-cell proliferation and FOXP3 expression in both healthy and RSV-infected infants. However, although IL-2 induced a similar pattern of STAT5 phosphorylation, the proliferative response of CD4 + T cells and the expression of FOXP3 + remained significantly lower in RSV-infected infants. Interestingly, we found a negative correlation between disease severity and both the production of IL-2 by CD4 + T cells and the ability of exogenous IL-2 to restore the pool of FOXP3 + CD4 + T cells. Conclusions A reduced ability to produce IL-2 and a limited response to this cytokine may affect the function of CD4 + T cells in RSV-infected infants.